1989
DOI: 10.1007/bf01540339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autonomic nervous system on gastric damage by ethanol in the rat

Abstract: To study whether or not the autonomic nervous system influences the defense mechanisms of the gastric mucosa, groups of Sprague-Dawley rats were given stimulants and inhibitors of the different components of the vagus and celiac nerves before administration of absolute or 70% w/v ethanol. The effects of vagotomy and sympathectomy on "adaptive cytoprotection" were studied, as were the effects of blocking the muscarinic receptors and stimulation of beta-adrenergic receptors. We found that: (1) cholinomimetic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…This could be explained by the fact that vagotomy, which would interfere with the signal transmission inside the capsaicin-sensitive afferent fibers of the vagus nerve, may adversely influence the defensive mechanism of the gas tric mucosa against ethanol-evoked damage [11,18]. It had been reported that the adaptive cytoprotection in duced by low concentration of ethanol was abolished by surgical vagotomy [ 19,20], In the present study, there was only a partial abolition of the cytoprotective action in duced by 20% ethanol after subdiaphragmatic vagotomy. Lidocaine completely abolished the protective action of 20% ethanol, it is therefore suggested that the enteric ner vous system seems to be important, in addition to possi ble involvement of the vagal reflex in such cytoprotective action.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that vagotomy, which would interfere with the signal transmission inside the capsaicin-sensitive afferent fibers of the vagus nerve, may adversely influence the defensive mechanism of the gas tric mucosa against ethanol-evoked damage [11,18]. It had been reported that the adaptive cytoprotection in duced by low concentration of ethanol was abolished by surgical vagotomy [ 19,20], In the present study, there was only a partial abolition of the cytoprotective action in duced by 20% ethanol after subdiaphragmatic vagotomy. Lidocaine completely abolished the protective action of 20% ethanol, it is therefore suggested that the enteric ner vous system seems to be important, in addition to possi ble involvement of the vagal reflex in such cytoprotective action.…”
Section: Discussionmentioning
confidence: 99%
“…There is little information regarding the role of the sympathetic nervous system in gastric mucosal defense. Sympathectomy has been reported to worsen damage by ethanol and to abolish adaptive protection in rats (27). N/OFQ is reported to decrease peripheral resistance and to increase blood flow to peripheral organs, including stomach, in the rat (34,35).…”
Section: Fig 5 Effect Of Pretreatment With Cgrpmentioning
confidence: 99%
“…Although controversial, there are studies in which vagotomy is reported to cause a tendency to worsen ethanol-induced lesions (27,28). Protection by peripherally administered prostaglandin E 2 , prostacyclin, and mild irritants (28,29) and by centrally administered TRH (18) is reduced in vagotomized rats.…”
Section: Fig 5 Effect Of Pretreatment With Cgrpmentioning
confidence: 99%
“…Hence, the possibility of having other potential mediators of adaptive cytoprotection had been evolved after the discovery of certain protective substances in the gastric luminal fluid of rats receiving a low concentration of HCl, which was unaffected by indomethacin. It was found that adaptive cytoprotection could be weakened or completely abolished after surgical sialoadenectomy, vagotomy or sympathectomy [5]. Since there is no unifying hypothesis regarding the mediation of adaptive cytoprotection, it is reasonable to assume that more than one mediator is involved in its mode of action, with the participation of multiple biological systems.…”
Section: Cytoprotection and Adaptive Cytoprotectionmentioning
confidence: 99%